Principles of training
This first issue of Coaching Science Abstracts reviews articles concerned with principles and factors associated with training program content Table of contents (these articles are available in long form): 1. SUMMARY OF TRAINING EFFECTS Shepard, R. J. (1978). Aerobic versus anaerobic training for success in various athletic events. Canadian Journal of Applied Sport Sciences, 3, 9-15. 2. ADAPTATIONS IN THE MITOCHONDRIA Noakes, T. (1986). Lore of running. Cape Town, South Africa: Oxford University Press. 3. CIRCADIAN RHYTHMS AND PERFORMANCE Rodahl, A., O'Brien, M. & Firth, P. G. (1976). Diurnal variation in performance of competitive swimmers. Journal of Sports Medicine and Physical Fitness, 16, 72-76. 4. DETRAINING Wilmore, J. & Costill, D. (1988). Physiological adaptations to physical training. In Training for sport and activity, Chapter 11. Dubuque, IA: Wm. C. Brown. 5. RETRAINING Wilmore, J. & Costill, D. (1988). Physiological adaptations to physical training. In Training for sport and activity, Chapter 11. Dubuque, IA: Wm. C. Brown. 6. TRAINING AND DETRAINING Rundell, K. W. (1994). Strength and endurance: Use it or lose it. Olympic Coach, 4(1), 7-9. 7. WHEN CEILING LEVELS OF FITNESS ARE REACHED IN SWIMMING Rushall Thoughts (1993). 8. EXERCISE AND BODY COMPOSITION IN WOMEN Ullrich, I., Bryner, R., Toffle, R. & Yeater, R. (1993). The effects of exercise intensity on body composition in women. Medicine and Science in Sports and Exercise, 25(5), Supplement abstract 316. 9. EXERCISE AND IMMUNOLOGY Nash, M. S., Nieman, D. C., Pedersen, B. K., Davis, J. M., Hoffman-Goetz, L. & Mackinnon, L. T. (1993). Exercise and immunology. Medicine and Science in Sports and Exercise, 25(5), Supplement abstract 123. 10. TRAINING RESPONSES IN SWIMMERS Bonen, A. & Kemp, N. H. (1977). Physiological, metabolic and practical considerations for training swimmers. Research Papers in Physical Education, 3(3), 10-15. 11. TRAINING LEVELS FOR SWIMMERS Sharp, R. L. (1993). Prescribing and evaluating interval training sets in swimming: a proposed model. Journal of Swimming Research, 9, 36-40. 12. AEROBIC TRAINING Madsen, O. (1983). Aerobic training: not so fast, there. Swimming Technique, November 1982-January 1983, 13-18. 13. AEROBIC AND ANAEROBIC IMPROVEMENTS AT THE SAME TIME Goforth, H. W., Jacobs, I. & Prusaczyk, W. K. (1994). Simultaneous enhancement of aerobic and anaerobic capacity. Medicine and Science in Sports and Exercise, 26(5), Supplement abstract 171. 14. AEROBIC TRAINING IS LIMITED IN CHILDREN Rowland, T. & Boyajian, A. (1994). Aerobic response to endurance training in children. Medicine and Science in Sports and Exercise, 26(5), Supplement abstract 468. 15. CROSS TRAINING SUPPORTED FOR GENERAL FITNESS Loy, S. F., Holland, G. J., Mutton, D. L., Snow, J., Vincent, W. J., Hoffmann, J. J. & Shaw, S. (1994). Effects of stair-climbing vs run Training on treadmill and track running performance. Medicine and Science in Sports and Exercise, 25(11), 1275-1278. 16. CROSS-TRAINING FOR AVERAGE PERSONS IS HELPFUL Mutton, D. L., Loy, S. F., Rogers, D. M., Holland, G. J., Vincent, W. J. & Heng, M. (1993). Effect of run vs combined cycle/run Training on VO2max and running performance. Medicine and Science in Exercise and Sports, 25(12), 1393-1397. 17. COMMENTS ON TRAINING CATEGORIES AND TRAINING PARAMETER VARIATIONS Rick L. Sharp (personal communication 30 August, 1994). 18. CHILDREN HAVE ONLY GENERAL METABOLIC RESPONSES Bar-Or, O. (1983). Pediatric sports medicine for the practitioner (comprehensive manual in pediatrics). New York, NY: Springer-Verlag. 19. STRENGTH AND ANAEROBIC RESPONSES IN YOUNG FEMALE RUNNERS Thorland, W. G., Johnson, G. O., Cisar, C. J., Housh, T. J. & Tharp, G. D. (1987). Strength and anaerobic responses of elite young female sprint and distance runners. Medicine and Science in Sports and Exercise, 19, 56-61. 20. TRAINING EFFECTS IN YOUNG BOYS (11-13 YR) Mero, A., Jaakkola, L. & Komi, P. V. (1991). Relationships between muscle fibre characteristics and physical performance capacity in trained athletic boys. Journal of Sports Sciences, 9, 161-171. 21. TRAINING EFFECTS ARE GENERAL IN YOUNG MALES Overend, T., Paterson, D., Cunningham, D. & Taylor, A. (1985, October). Interval and continuous training: A comparison of training effects. A paper given at the Annual Meeting of the Canadian Association of Sports Sciences, Laval University, Quebec. 22. FITNESS VARIATIONS IN ELITE ATHLETES Koutedakis, Y. (1995). Seasonal variation in fitness parameters in competitive athletes. Sports Medicine, 19, 373-392. 23. CRITICAL VELOCITY TEST FOR RUNNING Florence, S. L. & Weir, J. P. (1995). Relationship of critical velocity to marathon running performance. Medicine and Science in Sports and Exercise, 27(5), Supplement abstract 43. 24. ENERGY COST OF RUNNING MIDDLE-DISTANCES Hill, D. W. (1995). Energy cost of middle distance running races. Medicine and Science in Sports and Exercise, 27(5), Supplement abstract 45. 25. TIME OF DAY AND ANAEROBIC PERFORMANCE Lieferman, J. A., Jones, N. A., Dangelmaier, B. S., Dedrick, G. S., Burt, S. E., Swetmon, J. K. & Hill, D. W. (1995). Temporal specificity in exercise training. Medicine and Science in Sports and Exercise, 27(5), Supplement abstract 124. 26. ENERGY COST OF OLYMPIC KAYAKING EVENTS Fernandez, B., Perez-Landaluce, J., Rodriguez, M. & Terrados, N. (1995). Metabolic contribution in Olympic kayaking events. Medicine and Science in Sports and Exercise, 27(5), Supplement abstract 143. 27. TRAINING NOT ALWAYS OF A PHYSIOLOGICAL NATURE Myburgh, K. H., Lindsay, F. H., Hawley, J. A., Dennis, S. C. & Noakes, T. D. (1995). High-intensity training for 1 month improves performance but not muscle enzyme activities in high-trained cyclists. Medicine and Science in Sports and Exercise, 27(5), Supplement abstract 370. 28. AN ENERGY METABOLISM DIFFERENCE IN WOMEN Esbjornsson, M., Bodin, K. & Jansson, E. (1995). Muscle metabolism during a 30-s sprint test (Wingate Test) in females and males. Medicine and Science in Sports and Exercise, 27(5), Supplement abstract 448. 29. BODY SEGMENTS AND ROWING ERGOMETRY Kleshnev, V. & Kleshneva, E. (1995). Relationship of total work performance with part performance of main body segments during rowing ergometry. Medicine and Science in Sports and Exercise, 27(5), Supplement abstract 511. 30. SEX DIFFERENCES SHOWN IN ANAEROBIC RUNNING POWER TESTS Nummela, A. & Rusko, H. (1995). Gender differences in the determinants of maximal anaerobic running power. Medicine and Science in Sports and Exercise, 27(5), Supplement abstract 776. 31. TRAINING PRINCIPLES FOR MASTERS ATHLETES Rushall Thoughts, 1995. 32. ATTRIBUTES OF MIDDLE-DISTANCE RUNNING Brandon, L. J. (1995). Physiological factors associated with middle distance running performance. Sports Medicine, 19, 268-277.